Representation of Power and Nationalism in the Guided Democracy Material: A Perspective of Philosophy of Science and Wodak’s Critical Discourse Analysis - Ariwinata, Yuda; Fatimah, Siti (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
This study applies the Discourse-Historical Approach (DHA) within Critical Discourse Analysis (CDA) to examine how ideological power and nationalism were represented in Indonesian history education during the Guided Democracy era (1959–1965). Using textbooks, curriculum documents, and political speeches as primary data, the research explores how discourse functioned to legitimize Sukarno’s vision of “guided leadership,” unity, and revolutionary identity. The findings reveal that educational texts operated as ideological tools constructing a moral-political version of history that reinforced state authority and excluded plural perspectives. Through Fairclough’s and Wodak’s frameworks, the study identifies recurring lexical strategies—such as “revolutionary struggle” and “anti-imperialism”—as linguistic mechanisms shaping collective identity. The discussion extends to the postcolonial context, emphasizing that decolonizing education in Indonesia still faces epistemic dependency on state-centered and Eurocentric narratives. Aligning with recent scholarship on curriculum decolonization, the study concludes that historical education must move toward epistemic justice and critical pedagogy to reframe national identity and historical consciousness.